Adoption of global investment performance standards: Case of ASEAN - Deborah Zelikson; Moade Fawzi Shubita; JunJie Wu (Cogent Business & Management, 2020)
Research on voluntary compliance with accepted international standards has paid overwhelming attention to financial reporting standards, but not to investment performance standards. Previous research on the adoption of the Global Investment Performance Standards has overlooked the unique region of the Association of Southeast Asian Nations. Using 17 years (1999 to 2015) worth of data from all ten countries, which generates 170 country-year observations for each variable of the study, this paper evaluates whether, and how, social and economic pressures influence the adoption of GIPS in the region in the Institutional Theory lens. The results suggest that social pressure is more impactful than economic pressure on the adoption of GIPS. The findings have generated useful contributions and implications in this vein, and several future research directions have been identified.
Keywords: G11; G15; N95; P17; 650; Global Investment Performance Standards (GIPS); ASEAN; investment profession; regional integration; voluntary adoption; sustainability reporting; Chartered Financial Analyst (CFA)